Homework Help

How to prove -(a+b) = (-a)+ (-b)

jaxen28's profile pic

Posted via web

dislike 2 like
How to prove -(a+b) = (-a)+ (-b)

1 Answer | Add Yours

mvcdc's profile pic

Posted (Answer #1)

dislike 1 like

First of all, note that `-(a+b)` is equivalent to `-1*(a +b)` .

By the distributive property of multiplication, we have:

`(-1*a) + (-1*b)`

which can be simplified/written as:

`(-a) + (-b)` which is our desired expression.

------

Another solution:

`-(a+b) = -a - b = -a + (-b) = (-a) + (-b)` again, the desired expression.

Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes